2012 American Control Conference (ACC) 2012
DOI: 10.1109/acc.2012.6315283
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-based load control in power systems

Abstract: Abstract-Maintaining demand-supply balance and regulating frequency are key issues in power system control. Conventional approaches focus on adjusting the generation so that it follows the load. However, relying on solely regulating generation is inefficient, especially for power systems where contingencies like a sudden loss in generation or a sudden change in load frequently occur. We present a frequency-based load control scheme for demand-supply balancing and frequency regulation. We formulate a load contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, there are a lot of techniques used to predict and control the frequency of grid network to maintain stability, such as frequency response analysis, the dynamic simulation of the grid network also the steady state analysis of the grid network, which assumes that the grid is stable, load flow analysis [29] which is majorly used for power and voltage calculation can also be used to estimate the frequency of the grid network for different load values and since load values can be predicted in any power system network, then the corresponding frequency values can be determined. However, many literature [30][31][32][33][34][35][36][37][38][39] deals with frequency control in a power system network. The machine learning approach can be used to predict the frequency of the network based on the network's historical data and network topology.…”
Section: Annmentioning
confidence: 99%
“…However, there are a lot of techniques used to predict and control the frequency of grid network to maintain stability, such as frequency response analysis, the dynamic simulation of the grid network also the steady state analysis of the grid network, which assumes that the grid is stable, load flow analysis [29] which is majorly used for power and voltage calculation can also be used to estimate the frequency of the grid network for different load values and since load values can be predicted in any power system network, then the corresponding frequency values can be determined. However, many literature [30][31][32][33][34][35][36][37][38][39] deals with frequency control in a power system network. The machine learning approach can be used to predict the frequency of the network based on the network's historical data and network topology.…”
Section: Annmentioning
confidence: 99%
“…The distributed model predictive control method was proposed to control the output frequency of the power plant in order to decrease frequency fluctuations. The advantage of MPC is that it can be directly extended to multiple-input multiple-output (MIMO) systems, which can be quadratic, and take into account process constraints, making it impossible for variables to exceed predefined values [93,94].…”
Section: Mpc For Frequency Regulationmentioning
confidence: 99%
“…The availability of DR resources during peak load condition [19][20][21], and role of providing AS mainly in islanded distribution level based microgrids is given in [22][23][24][25][26]. A number of studies have been reported [5,6,8,[27][28][29][30][31][32][33] for efficacy of DR control loop for power grid frequency stabilization. The scope of DR loop offers additional merits to balance generation with load for LFC related issue.…”
mentioning
confidence: 99%
“…The general configuration for the analysis of effect of DR control loop on power system performance is not reported in [5,6,8,27,29,30,32,33]. Further, the robustness of controller against uncertainty and nonlinearities in the system have not been discussed in [5,6,8,9,[30][31][32][33][34]. Some specific load without generalization in the system is considered by [5,6] & [8,9].…”
mentioning
confidence: 99%